Postharvest quality of yellow passion fruit according to different rootstocks and growing environments - Botelho, Silvia de Carvalho Campos; Miguel-Wruck, Dulândula Silva; Roncatto, Givanildo; Oliveira, Suzinei Silva; Botelho, Fernando Mendes; Wobeto, Carmen (Comunicata Scientiae, 2017)
The objective of this study was to evaluate the influence of rootstocks on passion fruit physicochemical characteristics. The experiment was conducted in two properties in Terra Nova do Norte municipality, Mato Grosso State, Brazil. The experiment was conducted in a 2×8 factorial, in a completely randomized block design with four repetitions, being two growing environments (Environment 1 and Environment 2) and seven rootstocks with one control. The rootstocks used were: CPAC M5-H-67, H-CPAC MJ-65, CPAC MJ-45-03, CPAC MJ-H-68, Passiflora nitida (PN), P. alata (PA) and P. edulis (PE), under the canopy of a yellow passion fruit, BRS Gigante Amarelo cultivar. The same cultivar without rootstock was used as a control. The fruits were randomly harvest from each block. The following physical, physicochemical and chemical analysis were performed: weight, fruit length and diameter of the fruit, skin thickness, total soluble solids content (TSS), total acidity (TA), TSS/TA and vitamin C content. The use of rootstocks and rootstocks x environment interaction influenced the passion fruit physical characteristics. The environments influenced fruit quality, except for total acidity content. Environment 1 resulted in best fruit quality. For the Environment 2 no weight and length variation caused by rootstocks was observed. All analyzed rootstocks produced fruit with suitable characteristics for ‘in natura’ consumption or industrialization.